PENGEMBANGAN HARTA WAKAF DI SINGAPURA (Equilibrium: Jurnal Ekonomi Syariah, 2015)
Singapore is one of example   country which have been a success in organizing an waqf land. Various forms of productive endowments that is used in Singapore such as hotels, villas, offices and shops are succesful. This study aims to determine the model of development of waqf property in Singapore, using descriptive analysis. The results showed that the development of the productive waqf in Singapore is using istibdāl. Even in some cases, istibdāl considered as the most appropriate method to be used in developing and productive of waqf land. Many endowment assets are initially valued low and unproductive turned into high value and productive after istibdāl. Model istibdāl endowments in Singapore who applied were varied forms, such as endowments istibdāl models with similar replacement property, endowments istibdāl models with a replacement property that are not similar, collective endowments istibdāl models, and models istibdāl partial endowments. Singapura merupakan negara yang dinilai telah berhasil dalam mengembangkan dan memproduktifkan tanah wakaf. Berbagai bentuk wakaf produktif seperti hotel, vila, perkantoran dan pertokoan dibangun di atas tanah wakaf. Kajian ini bertujuan untuk mengetahui model pengembangan harta wakaf di Singapura dengan menggunakan analisis deskriptif. hasil kajian menunjukkan bahwa pembangunan wakaf produktif di Singapura adalah menggunakan metode istibdāl. Bahkan dalam beberapa kasus tertentu, istibdāl dianggap sebagai metode yang paling tepat untuk digunakan dalam mengembangkan dan memproduktifkan tanah wakaf. Banyak aset wakaf yang pada awalnya bernilai rendah dan tidak produktif berubah menjadi bernilai tinggi dan produktif setelah dilakukan istibdāl. Model istibdāl wakaf di singapura yang diaplikasikan pun beragam bentuknya, diantaranya adalah model istibdāl wakaf dengan harta benda pengganti yang sejenis, model istibdāl wakaf dengan harta benda pengganti yang tidak sejenis, model istibdāl wakaf kolektif, dan model istibdāl wakaf parsial.